Impact of field biomass burning on local pollution and long-range transport of PM2.5 in Northeast Asia. (January 2019) - Uranishi, Katsushige; Ikemori, Fumikazu; Shimadera, Hikari; Kondo, Akira; Sugata, Seiji
Abstract: Biomass burning (BB), such as, crop field burning during the post-harvest season, emits large amounts of air pollutants (e.g., PM2.5 ) that severely impact human health. However, it is challenging to evaluate the impact of BB on PM2.5 due to uncertainties in the size and location of sources as well as their temporal and spatial variability. This study focused on the impacts of BB on local pollution as well as the long-range transport of PM2.5 in Northeast Asia resulting from a huge field BB event in Northeast China during the autumn of 2014. Air quality simulations using the Community Multiscale Air Quality (CMAQ) model were conducted in the year 2014 over the horizontal domains covering Northeast Asia, including the Japanese mainland. In the baseline simulation (Base), field BB emissions were derived from Fire INventory from NCAR (FINN) v1.5 for the year 2014. The model reasonably captured the daily mean PM2.5 mass concentrations, however, it underestimated concentrations in autumn around Northeast China where irregular field BB following the harvest occurred frequently. To address the underestimation of emissions from BB sources in China, another simulation with boosted BB sources from cropland area (FINN20_crop) was conducted in addition to the Base simulation. The model performance of FINN20_crop was significantly improved and showed smaller biases and higher indices of agreement between simulated and observed values in comparison to those of Base. To evaluate long-range transport of PM2.5 from BB sources in China towards Japan, CMAQ with brute-force method (CMAQ/BFM)-estimated BB contributions for Base and FINN20_crop cases were compared with Positive Matrix Factorization (PMF)-estimated BB contributions at Noto Peninsula in Japan. The CMAQ/BFM-estimated contributions from FINN20_crop were in greater agreement with the PMF-estimated contributions. The comparison of BB contributions estimated by the two contrasting models also indicated large underestimations in the current BB emission estimates. Graphical abstract: Image 1 Highlights: This study focused on impact of huge field biomass burning in Northeast China in 2014. PM2.5 from biomass burning in China was transported to Japan during October 27–29. A baseline simulation underestimated the local and long-range transported pollution. A simulation with boosted biomass burning emissions indicated favorable performance. CMAQ and PMF combination enabled identification of bias in biomass burning emission. Abstract : This study revealed a large underestimation in the FINN emissions in Northeast China when evaluating the impact of field biomass burning on local pollution and long-range transport of PM2.5 .